Factors Associated with Healthy Preventive Behavior among the Elderly in Lamongan, East Java - Nurul Jannah; Didik Tamtomo; RB Soemanto (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Health promotion behaviors in the elderly have potential effects in promoting health and quality of life and reducing the cost of health care services. Changes in the lifestyle of the people affected by cardiovascular diseases have more potential shares in reducing vascular problems than medicinal treatments of hypertension and high cholesterol. By convincing more people to maintain and obtain healthy lifestyles, there will be considerable reduction in emergence and disabilities due to cardiac problems. This study aimed to determine factors associated with health preventive behavior among the elderly in Lamongan, East Java.Subjects and Method: This was a cross sectional study conducted in Lamongan, East Java, from November to December 2018. A sample of 200 elderly was selected by stratified random sampling. The dependent variable was health behavior. The independent variables were education, attitude, peer support, family support, cadre support, perceived behavioral control, subjective norm, and intention. The data were collected by questionnaire and analyzed by a multiple linear regression.Results: Health behavior in elderly was influenced by education (b = 0.76; 95% CI = 0.27 to 1.24; p = 0.002), intention (b= 0.08; 95% CI = 0.01 to 0.16; p = 0.033), attitude (b = 0.20; 95% CI = 0.07 to 0.33; p= 0.002), perceived behavioral control (b= 0.18; 95% CI= 0.06 to 0.30; p= 0.002), family support (b = 0.19 ; 95% CI = 0.08 to 0.30; p = 0.001), cadre support (b = 0.13; 95% CI = 0.04 to 0.23; p = 0.005), peer support (b = 0.07; 95% CI = - 0.01 to 0.15; p = 0.060), and subjective norm (b = 0.10; 95% CI = - 0.01 to 0.22; p = 0.064).Conclusion: Health behavior in elderly is influenced by education, intention, attitude, perceived behavioral control, family support, cadre support, peer support, and subjective norm.Keywords: health behavior, elderly, linear regressionCorrespondence: Nurul Jannah. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: njannah.31@gmail.com. Mobile: +6282230300405.Journal of Health Promotion and Behavior, 2018, 3(4): 223-229https://doi.org/10.26911/thejhpb.2018.03.04.01